Xylanase Production by Talaromyces amestolkiae Valuing Agroindustrial Byproducts - Barbieri, Giórgia S. [UNESP] (2022)
In general, agroindustrial byproducts can be easily assimilated by several microorganisms due to their composition, which is rich in carbohydrates. Therefore, they could be appropriate for use as raw materials in a sustainable refinery concept, including the production of hydrolytic enzymes with industrial applicability. In this work, xylanase production by the filamentous fungi Talaromyces amestolkiae in submerged culture was evaluated using five agroindustrial byproducts, namely, wheat bran, citrus pulp, rice bran, peanut skin, and peanut shell. Firstly, the aforementioned byproducts were characterized in terms of cellulose, xylan, lignin, and extractives. Next, production studies were performed, and wheat bran generated the highest enzymatic activity (5.4 U·mL−1), probably because of its large amount of xylan. Subsequently, a factorial design was performed to evaluate the independent variables yeast extract, wheat bran, K2HPO4, and pH, aiming to improve the variable response, xylanase activity. The condition that promoted the highest production, 13.02 U·mL−1 (141% higher than the initial condition), was 20 g·L−1 wheat bran, 2.5 g·L−1 yeast extract, 3 g·L−1 K2HPO4, and pH 7. Thus, industrial byproducts with a high content of xylan can be used as a culture medium to produce xylanase enzymes with a Talaromyces strain through an economical and sustainable approach.